2011
DOI: 10.1055/s-0031-1271677
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Strength Training in Children

Abstract: It has been demonstrated that strength training can be organized in children in a safe and effective way. However, there is limited data regarding its impact on muscle hypertrophy. This study investigated the effects of a high-intensity strength training (HIS) on knee extensor/flexor strength, countermovement (CMJ) jumping height, postural control, soft lean mass and muscle cross-sectional area (CSA) of the dominant leg in prepubertal children. Thirty-two children participated in this study and were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 29 publications
10
62
1
5
Order By: Relevance
“…Training-induced hypertrophy is the most likely mechanism to explain these findings. The effect of tennis on muscle size of the dominant arm observed in the present study is greater than the reported in healthy children using different strength training programs [1], [2], [3]. It is possible that the inclusion of plyometric movements in tennis strokes and not in the other studies [19], a higher training frequency in our TP (6 d/week) [6], together with a greater potential of the arms than the thighs for muscle hypertrophy [20], [21] may explain these differences.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Training-induced hypertrophy is the most likely mechanism to explain these findings. The effect of tennis on muscle size of the dominant arm observed in the present study is greater than the reported in healthy children using different strength training programs [1], [2], [3]. It is possible that the inclusion of plyometric movements in tennis strokes and not in the other studies [19], a higher training frequency in our TP (6 d/week) [6], together with a greater potential of the arms than the thighs for muscle hypertrophy [20], [21] may explain these differences.…”
Section: Discussioncontrasting
confidence: 70%
“…There is discrepancy about training-induced muscle hypertrophy in preadolescents [1], [2], [3]. It has been suggested that inadequate levels of circulating androgens [3] or training stimulus [4] may limit muscle hypertrophy before puberty.…”
Section: Introductionmentioning
confidence: 99%
“… %Δ, Percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; CSTS, core strength training on stable surface; CSTU, core strength training on unstable surface; EE, elbow extension; EF, elbow flexor; ET, elastic tubing; Ex, exercises; FFM, fat free mass; Freq, frequency; FW, free weight; Int, intensity; Isok, isokinetic; Isom, isometric; Isot, isotonic; KE, knee extension; KF, knee flexion; kg, kilogram; m, meter; Med, Medicine; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; PBT, plyometric training before balance training; PE, physical education students; PHV, peak height velocity; Post, post-test; Power, power measures; Pre, pre-test; PT, peak torque; Reps, repetitions; RM, repetition maximum; RPE, rating of perceived exertion; s, second; SD, standard deviation; Strength, strength measures; T, trained youth; TMS, trunk muscle strength; Tr, training status; U, untrained youth; Var, varied; Wks, weeks . Additional Citations for Table 2A are found in the text reference list (Hettinger, 1958; Funato et al, 1986; Sewall and Micheli, 1986; Weltman et al, 1986; Blimkie, 1989; Ozmun et al, 1994; DeRenne et al, 1996; Gorostiaga et al, 1999; Sadres et al, 2001; Flanagan et al, 2002; Pikosky et al, 2002; Tsolakis et al, 2004; Drinkwater et al, 2005; Benson et al, 2007; Faigenbaum et al, 2007a, 2014, 2015; Channell and Barfield, 2008; Rhea et al, 2008; Teng et al, 2008; Chelly et al, 2009; Dorgo et al, 2009; Lubans et al, 2010; Velez et al, 2010; Wong et al, 2010; Ebada, 2011; Granacher et al, 2011a,b, 2014, 2015; Ignjatovic et al, 2011; Muehlbauer et al, 2012; Santos and Janeira, 2012; Moore et al, 2013; Moraes et al, 2013; Sander et al, 2013; Coskun and Sahin, 2014; Ferrete et al, 2014; Pesta et al, 2014; Piazza et al, 2014; Dalamitros et al, 2015; Gonzalez-Badillo et al, 2015; dos Santos Cunha et al, 2015; Sarabia et al, 2015; Tran et al, 2015; Eather et al, 2016; Harries et al, 2016; Lloyd et al, 2016; Negra et al, 2016; Prieske et al, 2016; Rodriguez-Rosell et al, …”
Section: Resultsmentioning
confidence: 99%
“…During this period, sex differences in muscular strength begin to emerge, with boys demonstrating accelerated gains as a result of the adolescent spurt, and girls appearing to continue to develop in a more linear fashion 3. Potential factors inherently responsible for increases in strength during childhood appear to be related to the maturation of the central nervous system,47 for example, improvements in motor unit recruitment, firing frequency, synchronisation and neural myelination 48 49. Strength gains during adolescence are typically driven by further neural development, but structural and architectural changes resulting largely from increased hormonal concentrations, including testosterone, growth hormone and insulin-like growth factor play a significant role, especially in males 2.…”
Section: Effects Of Growth and Maturation On The Development Of Muscumentioning
confidence: 99%